Gene expression profiling of Trypanosoma cruzi in the presence of heme points to glycosomal metabolic adaptation of epimastigotes inside the vector. - Marcia C Paes; Francis M S Saraiva; Natália P Nogueira; Carolina S D Vieira; Felipe A Dias; Ana Rossini; Vitor Lima Coelho; Attilio Pane; Fei Sang; Marcos Alcocer (PLOS Neglected Tropical Diseases, 2020)
Chagas disease, also known as American trypanosomiasis, is a potentially life-threatening illness caused by the protozoan parasite, Trypanosoma cruzi, and is transmitted by triatomine insects during its blood meal. Proliferative epimastigotes forms thrive inside the insects in the presence of heme (iron protoporphyrin IX), an abundant product of blood digestion, however little is known about the metabolic outcome of this signaling molecule in the parasite. Trypanosomatids exhibit unusual gene transcription employing a polycistronic transcription mechanism through trans-splicing that regulates its life cycle. Using the Deep Seq transcriptome sequencing we characterized the heme induced transcriptome of epimastigotes and determined that most of the upregulated genes were related to glucose metabolism inside the glycosomes. These results were supported by the upregulation of glycosomal isoforms of PEPCK and fumarate reductase of heme-treated parasites, implying that the fermentation process was favored. Moreover, the downregulation of mitochondrial gene enzymes in the presence of heme also supported the hypothesis that heme shifts the parasite glycosomal glucose metabolism towards aerobic fermentation. These results are examples of the environmental metabolic plasticity inside the vector supporting ATP production, promoting epimastigotes proliferation and survival.